2022
DOI: 10.4028/p-9xgtbb
|View full text |Cite
|
Sign up to set email alerts
|

New Formula for Calculating Local Scour around Bridge Piers

Abstract: Several researchers working on the axes of solid particle transport, river flow, as well as the vulnerability of structures built on rivers have focused their work on the phenomenon of local scour, where many scour formulas have been proposed. Most of these formulas have been developed using laboratory data, estimated from simplified scaled-down models. This led to uncertainties and considerable inaccuracies in the scour estimation, sometimes causing serious consequences for the stability of structures subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Based on the PCA results, 5 variables were discarded from further analyses, and all remaining variables can be classified into the following categories: pier geometry (b, l, and bef), hydraulic (y, v, τ, and Fr), compounded hydraulic-sediment variables (vc, Frc, and Frd), sediment properties (d50, τc, and Rep), and channel properties (B and S). Previous studies have concluded that d50 can be eliminated from the development of the scour equation since its range of values is small when compared to the other variables, which consequently leads to biased results [19]. Since only field data are used in this study, d50 is expected to be negligible due to reaching large values of the ratio b/d50 [45,46].…”
Section: Variable Reductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the PCA results, 5 variables were discarded from further analyses, and all remaining variables can be classified into the following categories: pier geometry (b, l, and bef), hydraulic (y, v, τ, and Fr), compounded hydraulic-sediment variables (vc, Frc, and Frd), sediment properties (d50, τc, and Rep), and channel properties (B and S). Previous studies have concluded that d50 can be eliminated from the development of the scour equation since its range of values is small when compared to the other variables, which consequently leads to biased results [19]. Since only field data are used in this study, d50 is expected to be negligible due to reaching large values of the ratio b/d50 [45,46].…”
Section: Variable Reductionmentioning
confidence: 98%
“…With the aim of avoiding extrapolation issues, the accuracy of these models should be additionally confirmed with field measurements. Therefore, it is necessary to gain a perspective on scour potential under field conditions [19]. Regardless of the data collection method, most of the scour prediction equations are based on conventional regression methods to provide explicit expressions that are easy-to-use and readily applicable to practice.…”
Section: Introductionmentioning
confidence: 99%
“…Local scour is one of the main events that can threaten the stability of bridges built across rivers. This phenomenon appears as soil erosion on which the bridge piers are supported (Pandey & Md Azamathulla 2021), eventually collapsing the bridge with overall soil erosion (Annad & Lefkir 2022b;Devi & Kumar 2022). Owing to this phenomenon, significant losses in human life, property, and consequently the economy are continuously reported everywhere around the world (Toth & Brandimarte 2011;Bestawy et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have proposed various empirical formulas for predicting scour at bridges (Annad & Lefkir 2022b). However, it should be noted that most of the formulas claimed to calculate field scour at the bridge piers were developed using laboratory data, where these formulas have rarely been validated by field measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation